Cooperation and Discrimination Within and Across Language Borders: Evidence from Children in a Bilingual City - Silvia Angerer; Daniela Glätzle-Rützler; Philipp Lergetporer; Matthias Sutter (Institute for the Study of Labor (IZA), 2015)
We present experimental evidence from a bilingual city in Northern Italy on whether the language spoken by a partner in a prisoner's dilemma game affects behavior and leads to discrimination. Running a framed field experiment with 828 six- to eleven-year old primary school children in the city of Meran, we find that cooperation generally increases with age, but that the gap between cooperation among in-group members and cooperation towards children speaking another language is considerable and increasing with age. This gap is due to both, in-group favoritism and language group discrimination.
Keywords: C91; C93; D03; 330; cooperation; discrimination; language; children; experiment